Efeito de épocas de colheita e período de repouso pós-colheita sobre as características físicas de frutos e sementes de mamoneira - da Silva, Libia Belisario [UNESP]; Martins, Cibele Chalita [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
This study aimed to assess the effect of harvesting times and of post-harvest resting period on physical characteristics of fruits and seeds of castor bean (AL Guarany 2002 genotype) and to verify if theses characteristics could be used to identify the ideal harvest time. Nine times of raceme harvest were assessed from 30 to the 142 days after anthesis (DAA) at fourteen days intervals, and four conditions of resting; (without and with seven days of resting period of seeds extracted (bare), from fruits and fixed to the racemes). It was evaluated water content, seed thickness, and length, width, and weight of fresh fruits and seeds, and seedling emergence in sand. The statistical design was completely randomized with four replications. The harvest times and the post-harvest rest period affected the physical characteristics of fruits and seeds of castor bean but none of these have proved to be effective in the identification of the ideal harvest time.
Harvest periods and post-harvest resting period over physics characteristics of fruits and seeds in castor bean
Keywords: Phenology; maturation; Ricinus communis; AL Guarany 2002